On a Nonlinear Volterra Integral Equation in Two Variables - Pachpatte, B. G (Sarajevo Journal of Mathematics, 2024)
The aim of this paper is to study the existence, uniqueness and other properties of solutions of a certain nonlinear Volterra integral equation in two variables. The fundamental tools employed in the analysis are based on applications of the Banach fixed point theorem and a certain variant of the integral inequality with explicit estimate on the unknown function. 2000 Mathematics Subject Classification. 34K10, 35R10, 39A10